A preliminary study of the distributed maximum power point tracker designs for different types of solar cells in solar and electric vehicle arrays - Li, Q.; Wolfs, Peter (Engineers Australia, 2009)
For solar and electric vehicles, a highly distributed maximum power point tracking (MPPT) scheme is preferred. A maximum power point (MPP) tracker has been previously presented for a single triple junction cell. The Texas Instruments MSP430 microprocessor, which is designed for 1.8 V applications, provides the tracking intelligence. However, the MPP cell voltages of other cell types under different environmental conditions may fall well below 1.8 V. This paper conducts a preliminary study of four maximum power point tracker designs for different cell types, which cover an input supply voltage range from 0.3 to 3.0 V. A comparison of the applications, the topologies and the costs of the four designs is summarised at the end of the paper.